Current state and problems of innovative activity in Kazakhstan. (Journal of Economic Research & Business Administration, 2016)
Now interest of the Republic of Kazakhstan in innovative problems it is connected with scientific and technical development by social and economic development of the countries of the world.Generally at economic developments of the country, for planning of scientific and technical resources by the most important is formations of innovative and venture businesses.Through innovative activity the assessment is given for nature of innovative service, through this process it is possible to open essence of innovative activity.Generally in the country are realized increase in innovative activity through regional innovative development.Innovative activity of regions of Kazakhstan is a miscellaneous because, it it is connected with existence scientific and technical, financial, a manpower and opportunities of their use.Considering above-stated, in article current state and problems of innovative activity is provided in infrastructure of national economy.Problematic issues increase in innovative potential and increase in its activity are brought up.
Keywords: innovative activity; infrastructure of economy; market economy; innovative potential; innovative service.